PEMILIHAN TIPE PONDASI DALAM DENGAN MENGGUNAKAN METODE AHP - Mananoma, Tiny; Thalita D. Maratade, Anisya; A.Y Lapadengan, Tania Tazriana; Reza Mamuaya, Imanuel (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The environmental impact arising from the use of foundations that require limited heavy equipment maneuverability has become a recurring issue in construction projects. Construction sites located on clayey soils necessitate special treatment for foundation structures, consuming substantial time and resources. This poses a challenge in construction projects with tight schedules, as every construction phase is constrained by available funds. Data collected through interviews and questionnaires with relevant stakeholders are processed using the Analytical Hierarchy Process (AHP). Bore Pile foundations, is selected as the preferred choice. This research concludes that, among the options considered, Bore Pile foundations are the most suitable. It ranks second, with Well foundations in the second position and Pile foundations in the third. Therefore, Bore Pile foundations are recommended for construction projects in this context. It should be noted that this study is limited to the Gorontalo region's educational facilities, and further research is necessary for different locations. This research sheds light on the importance of selecting environmentally friendly foundation types in construction projects, particularly in regions with specific soil characteristics like clayey soil.